FARINHA MISTA DE TRIGO E BOCA´´IUVA: QUALIDADE TECNOLÓGICA E VIDA DE PRATELEIRA - OLIVEIRA, Letícia da Silva,; DONADON, Juliana Rodrigues,; HIANE, Priscila Aiko,; GUIMARÃES, Rita de Cassia Avellaneda, (ANAIS DO ENIC, 2023)
-